2001
DOI: 10.1159/000052943
|View full text |Cite
|
Sign up to set email alerts
|

Differential Levels of Interleukin 6 in Maternal and Cord Sera and Placenta in Women with Pre-Eclampsia

Abstract: Background: Interleukin 6 (IL-6) is a T helper 2 cytokine with a variety of properties including pro-inflammatory characteristics. It has, therefore, been implicated in the pathophysiology of abnormal pregnancies. Objective: To investigate the association between IL-6 and pre-eclampsia by estimating the differential levels of IL-6 in maternal and cord serum and supernatant of homogenized placental tissue. Methods: 50 primigravidae with pre-eclampsia and 50 matched normotensive primigravidae served as controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 22 publications
3
18
1
2
Order By: Relevance
“…The finding for IL-6 is in line with previous reports on elevated plasma levels of IL-6 in women with preeclampsia compared with normal pregnancies [18][19][20]. In contrast, Al-Othman et al found no difference in IL-6 levels in serum between preeclampsia and normal pregnancy [21]. We found increased levels of TNF-α for women with preeclampsia compared with normal pregnancies (P < 0.003).…”
Section: Discussionsupporting
confidence: 92%
“…The finding for IL-6 is in line with previous reports on elevated plasma levels of IL-6 in women with preeclampsia compared with normal pregnancies [18][19][20]. In contrast, Al-Othman et al found no difference in IL-6 levels in serum between preeclampsia and normal pregnancy [21]. We found increased levels of TNF-α for women with preeclampsia compared with normal pregnancies (P < 0.003).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, unlike the decidual cells, IL-6 immunostaining was localized primarily around the cell membranes in adjacent interstitial cytotrophoblasts. Previous publications observed that IL-6 expression was either unchanged 18,[32][33][34] or even reduced, 35 in preeclamptic versus control placentas, but did not specifically examine IL-6 expression in interstitial cytotrophoblasts. Therefore, this differential localization of IL-6 suggests a potential, previously undisclosed, paracrine interaction in which IL-6 is synthesized and secreted by decidual cells and then targets neighboring interstitial trophoblasts.…”
Section: Discussionmentioning
confidence: 96%
“…29 That IL-6 also interferes with endothelial cell function 30,31 suggests that preeclampsia-associated elevated plasma IL-6 levels contribute to the systemic endothelial activation and vascular damage that culminates in the maternal syndrome. Several studies examined the placenta as a source of excess circulating IL-6, but found that IL-6 expression was either unchanged 18,[32][33][34] or reduced 35 in preeclamptic versus control placentas.…”
mentioning
confidence: 99%
“…28 -30 TNF-␣ is known to activate other cytokines such as interleukin-6 (IL-6). 31,32 Although some studies suggest that the maternal and cord sera and placental levels of IL-6 may not be different between preeclamptic and normotensive women, 33 several other studies have shown that the plasma levels of IL-6 are elevated Ϸ2-to 3-fold in women with preeclampsia. 23,25,28,34 Additionally, our preliminary observations have shown that chronic elevation of plasma IL-6 Ϸ2-fold in late pregnant rats is associated with significant increases in blood pressure.…”
mentioning
confidence: 99%